PENGARUH PENGUMUMAN RIGHT ISSUE (SEBELUM DAN SESUDAH) TERHADAP RETURN SAHAM DAN VOLUME PERDAGANGANSAHAM PADA PERUSAHAAN FINANCE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2011-2014 - Farid Mukhlas; Rita Anugerah; Al Azhar L ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The research based on the analysis of the observation to the stock market condition in Indonesia about semi strong form efficiency in which market will react against an information. If the right issue contains information that the market react at the moment the right issue is published. The object of the research is to determine the influence of announcement right issue (before and after) to stock returns and trading volume stock on finance company listing indonesia stock exchange during 2011-2014. The method of the research is using event study with market adjusted model approach. The research sampling are the 33 corporate that registered in BEI during 2011-2014. Statistical test on stock return, and trading volume stock use t-test, paried two samples for mean on the period of announcement right issue. The result of this research based on statistics output shows that right issue announcement was responded by market in t -1, t0 and t +4. There is insignificant difference found in stock return before and after right issue , however trading volume stock shows the difference for the period obersvation before and after right issue.Keywords: stock market, right issue, stock return and trading volume stock.